Megastigmus transvaalensis (Hymenoptera: Torymidae) en Schinus polygamus (Anacardiaceae): Un nuevo huésped nativo para esta especie invasora que se alimenta de semillas - Fernandes, Daniell R. R.; Salas, Claudio [UNESP]; Rothmann, Sergio; Lara, Rogéria I. R.; Perioto, Nelson W. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2014)
This is the first report of the interaction between the seed-feeding M. transvaalensis and S. polygamous, a native fruit from South America.
Megastigmus transvaalensis (Hymenoptera: Torymidae) on Schinus polygamus (Anacardiaceae): A new native host for this invasive seed-feeding species
Keywords: Chalcidoidea; Chile; Megastigminae; Seed